Proceedings of the 2nd International Workshop on Software and Performance 2000
DOI: 10.1145/350391.350397
|View full text |Cite
|
Sign up to set email alerts
|

Visual representation of stochastic process algebra models

Abstract: Performance models are of increasing interest to professionals who do not have a background in mathematical analysis, it is important to provide additional mechanisms by developers may improve their confidence in the models they evaluate accurately reflect the systems they are studying. In this paper we discuss these issues, suggesting some basic techniques from program comprehension that be applied to models in a stochastic process algebra

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…The idea of visualising PEPA models is not a new one, and was first proposed in [27]. Since PEPA is a compositional language, we can view each component in the model independently, as an automaton whose transitions are labelled by activities.…”
Section: Visualisation Of Pepa Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…The idea of visualising PEPA models is not a new one, and was first proposed in [27]. Since PEPA is a compositional language, we can view each component in the model independently, as an automaton whose transitions are labelled by activities.…”
Section: Visualisation Of Pepa Modelsmentioning
confidence: 99%
“…Since PEPA is a compositional language, we can view each component in the model independently, as an automaton whose transitions are labelled by activities. In [27] it was suggested that we can do this by displaying the derivation graph of a component. We use a slightly different approach based on the Kronecker representation described in the previous section -this is entirely equivalent in terms of what the user sees, but the underlying data structure is more versatile, as we shall discuss in Section 6.…”
Section: Visualisation Of Pepa Modelsmentioning
confidence: 99%